THE DYNAMIC TRANSFORMATION OF ISLAMIC EDUCATIONAL INSTITUTIONS IN GAYO FROM 1900 TO 1986 - Ihsan Harun; Indra Indra; Emy Yusdiana (UIN Sumatera Utara Medan, 2021)
The dynamic development of Islamic education in Gayo cannot be separated from the turbulent period of education in Indonesia in general. The emergence and development and collapse of non-formal educational institutions and the transformation of formal institutions were influenced either directly or indirectly by the renewal of the dynamics of Islamic educational institutions in Indonesia. It was clear that the development of institutional transformation in Gayo from 1900 to 1986 was started by umah education. Graduates of homeschooling education usually continue their education to Mersah (musalla) or joyah for women of Gayo. These educational institutions are known as non-formal education. The formal education from 1900 to 1986 was started by Tarbiyah Islamiyah and Sekolah Rendah Islam (from 1902 to 1940). Meanwhile, in 1970 Pendidikan Guru Agama Pertama was established. Then, in 1980, this institution changed into Madrasah Aliyah Negeri 2 in Takengon. After that, in 1968 IAIN Persiapan was established in Temetas Lemah Burbana as Islamic higher education. However, this institution was transformed into Madrasah Aliyah Negeri 1 in Takengon in 1978. The Higher Education Institution was established in 1986 as a result of the transformation of STIE, STIT, and STIP into Perguruan Tinggi Gajah Putih Takengon. STIT tranformed into STAI Gajah Putih Takengon, and then it transformed into STAIN Gajah Putih Takengon, and today it is known as IAIN Takengon. Meanwhile, the STIE and STP transformed into Universitas Gajah Putih Takengon.